Análise de ofícios sob uma perspectiva bakhtiniana - Aquino, Wilton Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The objective of this work is to describe the particularities of the official letter genre, according to theoretical perspective of the Russian philosopher of language Bakhtin. The discourse genres, in this perspective, presented in relative stability, being affected by alterations occurred in the activity sphere where they circulate, for the ideological values that produce the speeches of this sphere and for the dialogic relations with other genres and spheres. It is intended to show as the official letter, in the public departments, although the stability acquired for its formal style, objective, reveals in an instability permeated for the thematic aspect, compositional and until stylistic. For realization of this analysis, were select sixty official letters of the public town administration sphere of the city of Araraquara, produced in the months of February, March and April of 2011. The official letters were separate in two groups for subject: repayment; diverse subjects. The methodology uses the dialogic boarding of the discourse used for the circle of Bakhtin

O objetivo desse trabalho é descrever as particularidades do gênero ofício segundo a perspectiva teórica do filósofo russo da linguagem Bakhtin. Os gêneros do discurso, nessa perspectiva, apresentam-se em relativa estabilidade, sendo afetados pelas alterações ocorridas na esfera de atividade em que eles circulam, pelos valores ideológicos que produzem os discursos dessa esfera e pelas relações dialógicas com outros gêneros e esferas. Pretende-se mostrar como o ofício, nas repartições públicas, apesar da estabilidade adquirida pelo seu estilo formal, objetivo, mostra-se numa instabilidade perpassada pelo aspecto temático, composicional e até estilístico. Para realização dessa análise foram selecionados sessenta ofícios da esfera pública municipal da cidade de Araraquara, produzidos nos meses de fevereiro, março e abril de 2011. Os ofícios foram separados em dois grupos por assunto: ressarcimentos; assuntos diversos. A metodologia utiliza a abordagem dialógica do discurso empregada pelo círculo de Bakhtin
Keywords: Bakhtin, M. M. (Mikhail Mikhailovich), 1895-1975; Análise do discurso; Official letter genre; Discourse genres; Bakhtinian studies; Discourse analysis